El Principio Universal y Constitucional de Movilidad Humana “Ciudadanía Universal”, La Limitación Económica del Estado y la Generación del Sentimiento de Xenofobia en la Población Ecuatoriana - Morocho Ruiz, Diana Carolina (2018)
This thesis is entitled: "The Universal and Constitutional Principle of Human Mobility" Universal Citizenship ", the Economic Limitation of the State and the Generation of the Feeling of xenophobia in the Ecuadorian Population", It is the product of the search for an answer to the problems raised in this research work, which is an important issue in our legislation. In the field of human mobility through its different modalities, it is believed that it is a utopian issue, where strong direct criticisms of conservatives from Ecuadorian society are received and based on current experience; There are social problems, economic instability, unemployment and tax evasion, causing feelings of xenophobia and related intolerance that is demonstrated through various forms of violence between Ecuadorians and emigrants and vice versa. This trend, in our country has been growing due to the recent social, economic and legal problems experienced by the countries of the world, has always been a voice of protest of the harmed sectors; because, much of the working class has been violated in their constitutional rights by the presence of foreigners that encourage job insecurity. This trend, in our country has been growing due to the recent social, economic and legal problems experienced by the countries of the world, has 5 always been a voice of protest of the harmed sectors; because, much of the working class has been violated in their constitutional rights by the presence of foreigners that encourage job insecurity. With the Constitution of 2008 has implemented a large catalog of guarantees, especially the recognition of universal citizenship, with this is intended that all foreigners residing in Ecuador enjoy the same guarantees as any Ecuadorian citizen. Given these circumstances, the Ecuadorian population generates a generalized criterion of feeling of xenophobia to foreigners, because the labor supply for the inhabitants of this country is reduced, having to resort to reducing the cost of their labor. The Constitution of the Republic of Ecuador guarantees in article 6 that all Ecuadorians are subjects of rights enshrined in this supreme norm; Given this panorama, the State must promote actions that lead to the achievement of the same in addition to the search for good living as a social and fundamental basis of the State. The approach of this research work would be to influence to achieve balance in what has to do with the application of rights for foreigners, where the presence of them does not undermine the constitutional rights of Ecuadorians. The theoretical, legal, doctrinal gathering, the application of surveys and interviews, allowed for a broad discussion of the topic, resulting in clear foundations on the subject matter. That is why I declare that, within the present topic analyzed, a transcendent discussion is proposed in the current reality of our State.